"We Learn How to Become Good Men": Working with Male Allies to Prevent Violence against Women and Girls in Urban Informal Settlements in Mumbai, India. (August 2020) - Chakraborty, Proshant; Osrin, David; Daruwalla, Nayreen
Engaging men has now become part of established global efforts to prevent violence against women and girls (VAWG), with most interventions focusing on making men's behaviors and attitudes more gender equitable. While scholarship on male allies has demonstrated the nature of their transformations and motivations, less attention has been paid to their negotiations of masculinity, privilege, the intersection between subjecthood and social contexts, and how these inform their engagements with women activists' anti-violence work in their communities. We explore questions of men's engagement in this article, which is based on a pilot ethnographic study with male allies in a VAWG prevention program in the informal settlements of Dharavi in Mumbai, India. We found that while men are able to acquire "knowledge" and "awareness" through the intervention, it produces an individuating effect wherein the structural nature of VAWG is obscured due to an emphasis on men's individual traits. This further informs participants' understanding of masculinity, which is marked by ambivalence as men negotiate multiple hegemonic masculinities and socioeconomic anxieties. One reason for this is that interventions with men are unable to destabilize public–private boundaries in informal settlements, which continue to treat VAWG as "private matters." We discuss the implications for local and global responses to engender accountability among male allies.